Overexpression of Activating Transcription Factor 3 Alleviates Cardiac Microvascular Ischemia/Reperfusion Injury in Rats - Liu, Yi; Hu, Yisen; Xiong, Jingjie; Zeng, Xiaocong (Frontiers in Pharmacology, 2021)
Activating transcription factor 3 (ATF3) has been confirmed to be responsive to oxidative stress and to negatively regulate the activity of Toll-like receptor 4 (TLR4). However, the effect of ATF3 on cardiac microvascular ischemia/reperfusion (I/R) injury remains unknown. The GEO2R online tool was employed to obtain differentially expressed genes (DEGs), GSE4015 and GSE120200, in two rat I/R injury microarray datasets. We established a rat myocardial I/R model in vivo, and also generated an in vitro hypoxia/reoxygenation (H/R) model of cardiomyoblast H9c2 cells. Overexpression of ATF3 was achieved by adenoviral-mediated gene transfer (Ad-ATF3). Rats were randomly divided into four groups: sham, I/R, I/R + Ad-Lacz (as a control), and I/R + ATF3. ELISA, CCK-8, DCFH-DA probe, qRT-PCR and Western blotting were used to determine the expression of ATF3, oxidative indices, cellular injury and TLR4/NF-κB pathway-associated proteins. Transmission electron microscopy, immunohistochemistry and immunofluorescence were used to detect the leukocyte infiltration and the alteration of microvascular morphology and function in vivo. Echocardiographic and hemodynamic data were also obtained. Bioinformatics analysis revealed that ATF3 was upregulated in I/R myocardia in two independent rat myocardial I/R models. Cardiac microvascular I/R injury included leukocyte infiltration, microvascular integrity disruption, and microvascular perfusion defect, which eventually resulted in the deterioration of hemodynamic parameters and heart function. Ad-ATF3 significantly restored microvascular function, increased cardiac microvascular perfusion, and improved hemodynamic parameters and heart function. Mechanistically, Ad-ATF3 ameliorated oxidative stress, inhibited TLR4/NF-κB pathway activation and down-regulated the expression of downstream proinflammatory cytokines in I/R myocardium in vivo and in H/R H9c2 cells in vitro. ATF3 overexpression protects against cardiac microvascular I/R injury in part by inhibiting the TLR4/NF-κB pathway and oxidative stress.